Alpha-calcium sulfate hemihydrate composite material and preparation method thereof
By adding nanomagnesium oxide to α-hemihydric calcium sulfate, the α-CSH composite material was prepared, and the problems of insufficient antibacterial properties and fast degradation speed of calcium sulfate materials were solved, and the efficient antibacterial and tissue regeneration effects of orthopedic implants and dental restoration materials were achieved.
Patent Information
- Application Number
- CN202510557507.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-29
- Publication Date
- 2025-08-01
AI Technical Summary
The existing calcium sulfate materials have insufficient antibacterial properties in orthopedic applications, and the degradation rate is faster than the new bone formation rate, and the addition of antibiotics, copper, silver ions or antimicrobial peptides has cytotoxic problems, making it difficult to meet the needs of bone repair and antibacterial.
Prepare α-hemihydrate calcium sulfate composite material. By adding nanomagnesium oxide (MgO) to α-hemihydrate calcium sulfate, α-CSH composite material is formed, adjusting its compressive strength and significantly enhancing its antibacterial properties. It is prepared by hydrothermal method and high-temperature curing process.
The compressive strength and toughness of the material have been improved, the solidification time is shortened, the antibacterial rate is increased to 99%, the biocompatibility is good, the risk of infection is reduced, and tissue healing is promoted. It is suitable for orthopedic implants and dental restoration materials.
Smart Images

Figure CN120398105A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of the preparation of biomedical materials, and particularly relates to an α-calcium hemisulfate composite material and a preparation method thereof. Background Art
[0002] Many orthopedic surgeries require bone grafting, such as trauma repair, tumor resection, joint revision, etc. Currently, a variety of materials (such as bioglass, bioceramics, metal materials) have been used, each with its own advantages and disadvantages. For example, autologous bone has osteoinductivity, but its source is limited and a second operation is required. Metal materials have high strength but are difficult to shape during surgery and are non-absorbable. Bioceramic bone repair materials (such as calcium phosphate, calcium sulfate, etc.) have good biocompatibility, but their mechanical properties cannot meet the requirements of weight-bearing. An ideal bone graft material should have a variety of good characteristics to meet clinical needs.
[0003] Calcium sulfate (CaS) is a bioceramic that can be shaped during surgery, is degradable, biocompatible, and supports bone regeneration, and has been gradually applied to clinical practice since the 1950s. However, CaS itself lacks antibacterial properties and is susceptible to infection. In existing reports, some researchers used a CaS-demineralized bone matrix composite material to treat 44 cases of nonunion after fracture, and the postoperative infection rate was 34%. Many research reports add antibacterial substances such as antibiotics, copper, silver ions, and antimicrobial peptides to CaS. However, antibiotics are prone to inducing drug resistance, copper and silver ions have cytotoxicity, and antimicrobial peptides are intolerant to sterilization. In addition, the degradation rate of CaS is faster than the rate of new bone formation, which is not conducive to bone defect repair. Therefore, it is still necessary to study new CaS-based bone graft materials with bone regeneration promotion and antibacterial properties.
[0004] Magnesium oxide (MgO) has strong antibacterial effects and good biocompatibility. In existing reports, some researchers found that MgO nanoparticles can not only effectively kill bacteria, but also kill fungi and viruses. Others found that MgO can not only reduce the formation of bacterial biofilms, but also inhibit the activity of bacteria in mature biofilms. Research reports show that MgO mainly kills bacteria through mechanisms such as reactive oxygen species (ROS) and mechanical damage. In addition, MgO can also enhance cell osteogenic differentiation and angiogenic differentiation through multiple pathways and by changing the bone microenvironment (the pH of the bone defect area and the Mg 2+ concentration). Qin Ling et al. found that Mg 2+ can directly promote the osteogenic differentiation of bone marrow mesenchymal stem cells, and Mg 2+ can also enter dorsal root ganglion (DRG) neurons through magnesium transporters and transient receptor potential cation channels to promote the expression of calcitonin gene-related peptide (CGRP), and CGRP further promotes the osteogenic differentiation of periosteal stem cells. The Qin Ling team also reported that Mg 2+ can enhance the expression of vascular endothelial growth factor (VEGF), facilitate vascular regeneration, and promote fracture healing; Mg 2+It can directly promote the polarization of macrophages into the M2 type. Magnesium also produces hydrogen gas, thereby inhibiting the inflammatory response and contributing to tissue regeneration. There is currently no research report on the antibacterial properties of CaS-MgO composites, nor any relevant reports on the in vivo antibacterial properties of MgO. Therefore, it is of great significance to develop a CaS-MgO composite material with antibacterial properties and biocompatibility in vitro and in vivo. Summary of the Invention
[0005] To solve the above problems, the present invention provides an α-calcium sulfate hemihydrate composite material and a preparation method thereof.
[0006] The first object of the present invention is to provide a preparation method of an α-calcium sulfate hemihydrate composite material, which specifically includes the following steps:
[0007] S1. Add sodium citrate and calcium sulfate hemihydrate to deionized water, mix evenly, and heat at 120-140 °C for 100-150 min;
[0008] S2. Place the mixed solution in step S1 in water not lower than 95 °C for repeated washing and precipitation, and then dry and pulverize the precipitate to obtain α-calcium sulfate hemihydrate powder;
[0009] S3. Mix MgO with α-calcium sulfate hemihydrate powder to obtain an α-calcium sulfate hemihydrate composite, where the mass fraction of MgO is 2.5-25%;
[0010] S4. Mix the α-calcium sulfate hemihydrate composite and distilled water in a certain proportion to make a slurry, pour it into a mold, and form a columnar sample through curing, which is the α-calcium sulfate hemihydrate composite material.
[0011] Preferably, the mass ratio of sodium citrate to calcium sulfate hemihydrate is 1:250-300.
[0012] Preferably, the mass ratio of sodium citrate to calcium sulfate hemihydrate is 1.5:400.
[0013] Preferably, the heating temperature in step S1 is 134 °C and the heating time is 120 min.
[0014] Preferably, the drying method in step S1 is drying in an oven, the drying temperature is 100 °C, and the time is 24 h; pulverization is carried out by high-speed pulverization using a wall breaker.
[0015] Preferably, the mass fraction of MgO in step S3 is 15-25%; the particle size of MgO is 50 nm.
[0016] Preferably, the ratio of the α-calcium sulfate hemihydrate composite to distilled water in step S4 is 2-3 g:1 mL.
[0017] Preferably, the curing in step S4 is high-temperature curing, the curing temperature is 90-100 °C, and the curing time is 4-8 hours.
[0018] Preferably, the α-calcium hemihydrate sulfate powder is short rod-shaped crystals, with a length of 50-80 μm and a diameter of 20-40 μm; the mold specifications are Φ5×5 mm, Φ5×10 mm or Φ10×10 mm.
[0019] The second object of the present invention is to provide an α-calcium hemihydrate sulfate composite material, which is prepared by a preparation method of an α-calcium hemihydrate sulfate composite material.
[0020] Compared with the prior art, the present invention can achieve the following beneficial effects:
[0021] (1) Improvement in mechanical properties: By adding different proportions of nano-magnesium oxide (MgO), the compressive strength of the α-CSH composite material can be adjusted. Although the compressive strength decreases with the increase in the proportion of MgO, the toughness and durability of the material may be improved, making it more suitable for applications such as bone repair.
[0022] (2) Shortening of the setting time: Compared with pure α-CSH, the initial setting and final setting times of the composite material added with MgO are significantly shortened, which helps to improve the operability and molding efficiency of the material in practical applications.
[0023] (3) Significantly enhanced antibacterial properties: With the increase in the proportion of MgO, the antibacterial rates of the composite material against Escherichia coli and Staphylococcus aureus are significantly increased, up to 99% at most. The improvement in antibacterial properties is attributed to the antibacterial activity of MgO and its uniform distribution in the composite material. The composite material containing MgO can form an obvious antibacterial zone, and the diameter increases with the increase in the proportion of MgO. It shows that the composite material can effectively inhibit bacterial growth and reduce the risk of infection. Inhibition of biofilm formation: The composite material significantly reduces the ability of bacteria to form biofilms, which is of great significance for preventing medical device-related infections and improving the long-term stability of bone repair materials.
[0024] (4) Good biocompatibility: The composite materials with low proportions of MgO (such as 2.5% and 7.5%) show good cell compatibility and high cell viability; it indicates that these materials will not cause obvious cytotoxic reactions when applied in vivo. The composite material can promote the expression of alkaline phosphatase (ALP) in MC3T3 cells and enhance osteogenic ability. In addition, it also has a significant promoting effect on the angiogenesis ability of human umbilical vein endothelial cells (HUVECs), which helps to accelerate wound healing and tissue regeneration.
[0025] (5) Significant in vivo antibacterial effect: In a rat model, the composite material containing MgO significantly reduced the number of bacteria at the implant site, with an antibacterial rate of up to 98.9%. In addition, histological examinations showed that these materials were able to reduce inflammatory responses and promote tissue healing. Reduced inflammatory response: Compared with pure α-CSH, the composite material containing MgO significantly reduced the white blood cell count and inflammatory cell aggregation at the implant site, indicating that it has better biocompatibility and anti-inflammatory ability.
[0026] (6) Simple preparation process and adjustable parameters: α-CSH composite materials can be efficiently prepared through conventional processes such as hydrothermal method and high-temperature curing. The operation is simple and easy to scale up. By adjusting the proportion of MgO, curing conditions and mold size, the performance of the material can be optimized to meet the needs of different application scenarios.
[0027] In summary, the composite material prepared by the present invention not only has good mechanical properties and biocompatibility, but also has significant antibacterial ability. It is a multifunctional material that integrates bone repair, antibacterial and tissue regeneration functions. It has broad application prospects in the fields of orthopedic implants, dental restorative materials and wound dressings, and can effectively reduce the risk of infection and promote tissue healing. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The microstructure of α-calcium sulfate hemihydrate (α-CSH) powder provided by an embodiment of the present invention under a scanning electron microscope is shown.
[0029] Figure 2 1 is the XRD result of α-calcium sulfate hemihydrate (α-CSH) powder provided according to an embodiment of the present invention.
[0030] Figure 3 This is a comparison of the initial setting time and final setting time of each material provided by the present invention.
[0031] Figure 4 is a result of the compressive strength of the respective materials provided according to the present invention.
[0032] Figure 5 This is the in vitro degradation result of each material provided by the present invention.
[0033] Figure 6 This is the pH change result during the in vitro degradation of each material provided by the present invention.
[0034] Figure 7 This is the result of the generation of active oxygen inside and outside the cells according to the materials provided by the present invention.
[0035] Figure 8 It is the absorbance result of PBS solution of each material provided according to the present invention.
[0036] Figure 9 are the antibacterial and antibacterial rate results of each material provided by the present invention against Escherichia coli and Staphylococcus aureus.
[0037] Figure 10 are the antibacterial zone results of each material provided by the present invention against Escherichia coli and Staphylococcus aureus.
[0038] Figure 11 are the results after crystal violet staining of the biofilms formed by each material provided by the present invention.
[0039] Figure 12 are the absorbance results after crystal violet staining and elution of the biofilms formed by each material provided by the present invention.
[0040] Figure 13 is the influence of the MgO addition ratio in each material provided by the present invention on cell viability.
[0041] Figure 14 is a schematic diagram of the results of the proportion of live cells and dead cells affected by the MgO addition ratio in each material provided by the present invention.
[0042] Figure 15 is the influence of each material with different MgO addition ratios provided by the present invention on the expression of alkaline phosphatase (ALP).
[0043] Figure 16 is the evaluation result of the angiogenesis ability of each material provided by the present invention.
[0044] Figure 17 is the result of the influence of each material provided by the present invention on the antibacterial activity in rats. Detailed implementation manners
[0045] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. In the following description, the same modules are denoted by the same reference numerals. In the case of the same reference numerals, their names and functions are also the same. Therefore, their detailed descriptions will not be repeated.
[0046] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention, but do not constitute a limitation to the present invention.
[0047] The sources of the reagents used in the present invention are as follows: sodium citrate (Na3C6H5O7·2H2O), Macklin biochemical reagent; calcium sulfate hemihydrate (CaSO4·1 / 2H2O), Kelong Chemical; magnesium oxide (MgO, particle size 50 nm), Macklin.
[0048] The present invention provides a method for preparing an α-calcium sulfate hemihydrate composite material, which specifically includes the following steps:
[0049] S1. Add sodium citrate and calcium sulfate hemihydrate to deionized water, mix evenly, and heat at 120 - 140 °C for 100 - 150 min;
[0050] Specifically, the mass ratio of sodium citrate to calcium sulfate hemihydrate is 1:250 - 300; in a specific embodiment, the mass ratio of sodium citrate to calcium sulfate hemihydrate is 1.5:400;
[0051] In a specific embodiment, the heating temperature is 134 °C and the heating time is 120 min;
[0052] S2. Place the mixed solution in step S1 in boiling water (>95 °C) for repeated washing and precipitation, then dry and crush the precipitate to obtain α-calcium sulfate hemihydrate (α-CSH) powder;
[0053] Specifically, the drying method is drying in an oven, the drying temperature is 100 °C, and the time is 24 h; the crushing is carried out by high-speed crushing with a wall breaker;
[0054] S3. Mix MgO with α-calcium sulfate hemihydrate (α-CSH) powder to obtain an α-calcium sulfate hemihydrate composite, where the mass fraction of MgO is 2.5 - 25%;
[0055] Specifically, the particle size of MgO is 50 nm; in specific embodiments, the mass fractions of MgO are 2.5%, 7.5%, 15%, and 25%; MgO is used as a filler or modifier to improve the performance of α-CSH; for example, it can improve the compressive strength, durability, or chemical stability of the material;
[0056] S4. Mix 2 - 3 g of the α-calcium sulfate hemihydrate composite and 1 mL of distilled water in proportion, make a slurry, pour it into a mold, and form a columnar sample through curing, which is the α-calcium sulfate hemihydrate composite material;
[0057] Specifically, the mold specifications are Φ5×5 mm, Φ5×10 mm, or Φ10×10 mm; the curing conditions include high-temperature curing, normal-temperature curing, etc.; the temperature of high-temperature curing is specifically 90 - 100 °C, and the curing time is 4 - 8 hours. In this step, the curing conditions of the α-calcium sulfate hemihydrate composite slurry include but are not limited to appropriate solid-liquid ratio, curing time, curing temperature, and mold size, etc. By adjusting the parameters, the mechanical properties and biocompatibility of the material can be optimized; the selection of specific parameters can be adjusted according to the application scenario and performance requirements of the material.
[0058] Example 1
[0059] This embodiment provides a method for preparing an α-calcium sulfate hemihydrate composite material, which specifically includes the following steps:
[0060] S1. Add sodium citrate and calcium sulfate hemihydrate to deionized water, mix evenly; place it in a hydrothermal sterilizer and heat at 134 °C for 120 min; the mass ratio of sodium citrate to calcium sulfate hemihydrate is 1.5:400;
[0061] S2. Place the mixed solution in step S1 in an oven at 100 °C, and repeatedly wash and precipitate it in boiling water (>95 °C), then dry and crush the precipitate to obtain α-calcium sulfate hemihydrate (α-CSH) powder; the drying temperature is 100 °C and the time is 24 h; the crushing is carried out by high-speed crushing with a wall breaker; the α-calcium sulfate hemihydrate (α-CSH) powder is a short rod-shaped crystal (length 50 - 80 μm, diameter 20 - 40 μm), and the surface is smooth.
[0062] S3. Mix MgO with α-calcium sulfate hemihydrate (α-CSH) powder to obtain an α-calcium sulfate hemihydrate composite, where the mass fraction of MgO is 2.5%, and the particle size of MgO is 50 nm;
[0063] S4. Mix 10 g of the α-calcium sulfate hemihydrate composite and 4 mL of distilled water according to the ratio, make it into a slurry, pour it into a mold, and form a columnar sample through curing, which is the α-calcium sulfate hemihydrate composite material; the mold specifications are Φ5×5 mm, Φ5×10 mm or Φ10×10 mm; the curing condition is high-temperature curing, the temperature is specifically 100 °C, and the curing time is 5 hours.
[0064] Example 2
[0065] This embodiment provides a method for preparing an α-calcium sulfate hemihydrate composite material, where: the mass fraction of MgO in step S3 is 7.5%; the other steps are the same as in Example 1.
[0066] Example 3
[0067] This embodiment provides a method for preparing an α-calcium sulfate hemihydrate composite material, where: the mass fraction of MgO in step S3 is 15%; the other steps are the same as in Example 1.
[0068] Example 4
[0069] This embodiment provides a method for preparing an α-calcium sulfate hemihydrate composite material, where: the mass fraction of MgO in step S3 is 25%; the other steps are the same as in Example 1.
[0070] Example 5
[0071] This embodiment provides a method for preparing an α-calcium sulfate hemihydrate composite material, wherein: in step S4, the curing conditions are: the curing temperature is 90 °C and the curing time is 8 hours; the remaining steps are the same as in Example 4.
[0072] Example 6
[0073] This embodiment provides a method for preparing an α-calcium sulfate hemihydrate composite material, wherein: in step S1, the mass ratio of sodium citrate to calcium sulfate hemihydrate is 1:300; the remaining steps are the same as in Example 4.
[0074] Comparative Example 1
[0075] This comparative example provides a method for preparing an α-calcium sulfate hemihydrate material, which specifically includes the following steps:
[0076] S1. Add sodium citrate and calcium sulfate hemihydrate to deionized water, mix evenly; place it in a hydrothermal sterilizer and heat at 134 °C for 120 min; the mass ratio of sodium citrate to calcium sulfate hemihydrate is 1.5:400;
[0077] S2. Place the mixed solution in step S1 in an oven at 100 °C, and wash and precipitate it repeatedly in boiling water (>95 °C), then dry and crush the precipitate to obtain α-calcium sulfate hemihydrate (α-CSH) powder; the drying temperature is 100 °C and the time is 24 h; the crushing is carried out by high-speed crushing with a wall breaker;
[0078] S4. Mix 10 g of α-calcium sulfate hemihydrate (α-CSH) powder and 4 mL of distilled water in proportion to make a slurry, pour it into a mold, and form a columnar sample through curing, which is the α-calcium sulfate hemihydrate composite material; the mold specifications are Φ5×5 mm, Φ5×10 mm or Φ10×10 mm; the curing conditions are high-temperature curing, the temperature is specifically 100 °C, and the curing time is 5 hours.
[0079] Perform physical and chemical property tests on the α-calcium sulfate hemihydrate composite materials and α-calcium sulfate hemihydrate materials prepared in Examples 1 to 4 and Comparative Example 1; for the sake of simplicity of expression, the abbreviations of each example are as follows: CaS-2.5% MgO, CaS-7.5% MgO, CaS-15% MgO, CaS-25% MgO, and CaS group; the specific process and results are as follows:
[0080] I. Material Characterization
[0081] The surface morphology and crystal phase of α-CSH were studied using a scanning electron microscope (EM6900, Zhongke Keyi) and an X-ray diffractometer (TD-3500, Tongda Technology), respectively. The initial and final setting times of the materials were determined using the Gillmore double-needle method. The compressive strength of the samples (Φ10×10 mm) was tested using a universal testing machine (E3000, Instron, USA) at a speed of 1 mm / min. The samples were immersed in phosphate buffer solution (PBS, pH 7.40, 37 °C, shaking water bath at 180 rpm) at a ratio of 0.2 g:1 ml for a specified time and then taken out, thoroughly dried (60 °C, 12 h) and weighed; the in vitro degradation rate was calculated based on the mass loss. In addition, the samples were immersed in 8 ml of PBS at this solid-liquid ratio for 14 d, and the pH value was measured at specified time points to determine the pH change trend during the in vitro degradation process of the samples.
[0082] The results of the morphology and crystal phase are as Figure 1 - Figure 2 shown; Figure 1 Scanning electron microscopy observations showed that the particle size of the α-CSH powder was relatively uniform, and it was a short rod-shaped crystal (length 50 - 80 μm, diameter 20 - 40 μm) with a smooth surface. Figure 2 The XRD results showed that the main diffraction peaks of the samples matched the typical diffraction angles of CSH.
[0083] The results of the setting time and compressive strength are shown in Figure 3 - Figure 4 . The initial setting and final setting time ranges of all samples were 6 - 7 min and 10 - 14 min, respectively ( Figure 3 ). Compared with the CaS group, the initial setting times of CaS-2.5% MgO, CaS-7.5% MgO, CaS-15% MgO, and CaS-25% MgO were shortened by 1%, 8%, 11%, and 14%, respectively; the final setting times were shortened by 22%, 23%, 24%, and 24%, respectively. The compressive strength of the samples decreased with the increase in the MgO ratio ( Figure 4 ); compared with CaS, the compressive strengths of the other 4 groups were reduced by 15%, 24%, 56%, and 57%, respectively.
[0084] The results of the in vitro degradation are shown in Figure 5 ; the samples in each group showed a nearly uniform weight loss in PBS. At all time points, the weight loss rate was negatively correlated with the MgO ratio. By the 14th day, the weight loss rates of each group were 60 ± 3% (CaS), 54 ± 3% (CaS-2.5% MgO), 50 ± 3% (CaS-7.5% MgO), 48 ± 5% (CaS-15% MgO), and 44 ± 2% (CaS-25% MgO), respectively.
[0085] The results of the pH change during the in vitro degradation are shown in Figure 6; In the in vitro degradation test, at all time points, the pH value of PBS increased with the increase in the proportion of MgO. The pH value of the CaS group rapidly decreased from 7.3 and reached ~5.52 at 12 h, and then remained relatively stable until the end of the test (336 h). In the other groups, the pH value first decreased and then increased, and finally gradually stabilized. The pH value of CaS-2.5% MgO decreased to ~5.75 at 24 h, then gradually increased and stabilized at 6.19 at 240 h. The pH values of the other three groups reached the lowest values at 24 h (CaS-7.5% MgO) or 48 h (CaS-15% MgO, CaS-25% MgO), then gradually increased, and stabilized at 7.25, 7.49, and 7.78 at 192 h, respectively.
[0086] II. Detection of intracellular and extracellular reactive oxygen species (ROS)
[0087] MC3T3 cells (Shanghai Saibakang Biotechnology) were added to α-MEM medium (Gibco, USA) and cultured adherently after resuscitation (Thermo 330N incubator, 37 °C, 95% humidity, 5% CO2) for 1 week, and then digested with trypsin (Shanghai Beyotime Biotechnology); after centrifugation of the digestion solution (1000 rpm, 3 min), the cell pellet was resuspended, counted and adjusted to 10 5 / ml. The cell suspension was inoculated into a 24-well plate (500 μl / well), cultured for 4 h to adhere and then cultured for another 24 h. The sample (Φ5×10 mm) was placed into the well, taken out after co-culturing with the cells for 6 h. After gently rinsing the bottom of the well with PBS (500 μl×3), 150 μl of α-MEM containing 10 μM ROS fluorescent probe (2′,7′-dichlorodihydrofluorescein diacetate, DCFH-DA) was added to each well, and incubated in the dark for 10 min and then the liquid was aspirated; after gently rinsing the well plate with PBS, the fluorescence generated inside the cells was observed under a fluorescence microscope ((Olympus IX73)). Nitroblue tetrazolium (superoxide ion probe) (NBT, Beijing Solarbio Science & Technology) was dissolved in dimethyl sulfoxide (Kelong Chemistry) at 600 μM / ml. 360 μl of this solution was mixed with 35.6 ml of PBS. 1 g of the sample was immersed in 2 ml of this mixed solution for 30 min, and then the absorbance at 560 nm of the immersion solution (the reaction product of NBT and ROS) was measured (GeneTech microplate reader, USA).
[0088] The results of ROS generation inside and outside the cells are shown in Figure 7 - Figure 8 . DCFH-DA is hydrolyzed into dichlorodihydrofluorescein (DCFH) inside the cells, and DCFH is oxidized by ROS inside the cells into dichlorofluorescein and produces green fluorescence under a fluorescence microscope. Figure 7 In A of, compared with the blank control group (without sample stimulation), the number of cells producing green fluorescence in the remaining groups increased with the increase in the proportion of MgO. Quantitative measurement found that (Figure 7 B), compared with the blank control group, the proportion of green fluorescent cells in each sample group increased by 45% (CaS), 109% (CaS - 2.5% MgO), 239% (CaS - 7.5% MgO), 538% (CaS - 15% MgO), and 716% (CaS - 25% MgO), respectively. There was no significant difference among the four experimental groups (control group vs. CaS group, control group vs. CaS - 2.5% MgO group, CaS group vs. CaS - 2.5% MgO group, CaS - 2.5% MgO group vs. CaS - 7.5% MgO group). There were significant differences among the other pairs.
[0089] As Figure 8 shown, ROS generation experiments were also carried out in cell-free PBS. It was also found that as the proportion of MgO in the sample increased, the absorbance of PBS gradually increased. Compared with CaS, the absorbance increased by 126 - 323 from CaS - 2.5% MgO to CaS - 25% MgO. There was no significant difference between the control group and the CaS group, and between the CaS - 2.5% MgO group and the CaS - 7.5% MgO group. There were significant differences among the other pairs.
[0090] III. In vitro antibacterial test
[0091] 1. Antibacterial rate: After resuscitating Escherichia coli (CMCC44102) and Staphylococcus aureus (CMCC26003) (both purchased from Nanjing Bianzhen Biotechnology Co., Ltd.), a bacterial suspension with a concentration of 10 5 CFU / ml (when the absorbance at 600 nm is about 0.2, the concentration is 10 8 CFU / ml) was prepared. The samples (Φ5×5 mm) were placed in a 96-well plate, and 200 μl of the bacterial suspension was added to each well and co-cultured for 24 h. The wells containing only the bacterial suspension were used as the negative control group. After taking out the plate, the bacteria on the surface of the samples were blown into the solution and mixed evenly. 150 μl of the bacterial suspension was collected and serially diluted 10 6 times in a 1:10 ratio. 150 μl of the diluted bacterial suspension was evenly spread on an agar plate and incubated for 24 h (incubator, 37 °C), and then the colonies were observed and counted. The antibacterial rate was calculated as follows: Antibacterial rate = [ (number of colonies in the control group) - (number of colonies in the sample group) ] / (number of colonies in the control group).
[0092] Results: For both bacteria, the antibacterial rate increased monotonically with the proportion of MgO ( Figure 9)。The antibacterial rate of the CaS group against both bacteria was 17%. The antibacterial rates of each MgO-containing group against Escherichia coli were from 87.5 ± 5.6% (CaS-2.5% MgO) to 99.0 ± 0.5% (CaS-25% MgO), and those against Staphylococcus aureus were from 91.5 ± 5.6% to 99.0 ± 0.5%. For both bacteria, the differences between the CaS group and any other group were statistically significant. Due to the great differences between the CaS group and all other groups, the differences between all MgO-containing groups were not statistically significant.
[0093] 2. Inhibition zone: Mix 1 ml of bacterial solution (10 8 CFU / ml) with 15 ml of agar liquid and pour it into a petri dish, and bury the sample (Φ5×5 mm) in the agar. After the agar cools and solidifies, incubate it upside down (37 °C, 24 h). Measure the diameter of the inhibition zone with a vernier caliper, and measure each inhibition zone 3 times and take the average value.
[0094] The results are shown in Figure 10 : No formation of inhibition zones was observed in the CaS group at all time points (1 - 10 d), while inhibition zones were formed in other groups and the diameters increased with the increase in the MgO ratio. In the antibacterial test of Escherichia coli ( Figure 10 in A, C, E, G), after culturing for 1 d, the diameters of the inhibition zones of CaS-2.5% MgO to CaS-25% MgO increased by 290%; there was no statistically significant difference between CaS-7.5% MgO and CaS-15% MgO, and between CaS-7.5% MgO and CaS-15% MgO, and statistically significant differences were found between the remaining pairs. In the antibacterial experiment of Staphylococcus aureus ( Figure 10 in B, D, F, H), the diameters of the inhibition zones of CaS-2.5% MgO to CaS-25% MgO increased by 113%; there were statistically significant differences between CaS-2.5% MgO and CaS-15% MgO, and between CaS-2.5% MgO and CaS-25% MgO, and no statistically significant differences were found between the other pairs. From 1 d to 10 d, the diameters of the inhibition zones of both bacteria generally showed a slight shrinking trend. In the antibacterial test of Escherichia coli, compared with the 1st d, the diameters of the inhibition zones on the 10th d decreased by 16% (CaS-2.5% MgO), 18% (CaS-7.5% MgO), 14% (CaS-15% MgO), and 9% (CaS-25% MgO) respectively. In the antibacterial test of Staphylococcus aureus, the diameters of the inhibition zones of the above groups decreased by 30%, 14%, 17%, and 14% respectively.
[0095] IV. Biofilm quantification
[0096] 1. Effect on biofilm formation: Place the samples (Φ5×10 mm) in a 24-well plate, add 1 ml of bacterial solution to each well, and incubate for 24 h. Take out the samples, rinse with normal saline and then fix with methanol for 15 min. Aspirate the methanol and air-dry the samples. Immerse the samples in a 1% (w / v) crystal violet (company) solution for 15 min, and then rinse with a large amount of PBS until the rinse solution is visually colorless. Immerse the samples in 1 ml of 33% (v / v) glacial acetic acid to dissolve and release crystal violet, and measure the absorbance of the solution (590 nm).
[0097] The results showed that the surfaces of the samples in each group were blue after crystal violet staining, and the depth became shallower in turn with the increase of the MgO ratio, indicating that the ability of the samples to resist biofilm formation was enhanced ( Figure 11 ). After eluting crystal violet with glacial acetic acid, the absorbance of the eluate decreased with the increase of MgO. In the co-culture experiment of Escherichia coli, compared with the CaS group, the absorbance of the eluate in the other groups decreased by 18.1% (CaS-2.5% MgO), 43.0% (CaS-7.5% MgO), 50.6% (CaS-15% MgO), and 60.9% (CaS-25% MgO) in turn. In the co-culture experiment of Staphylococcus aureus, the samples in each group decreased by 11.5%, 44.6%, 51.6%, and 62.0% in turn. For the two bacteria, there was no significant difference between the 4 pairs of experimental groups (CaS and CaS-2.5% MgO, CaS-7.5% MgO and CaS-15% MgO, CaS-7.5% MgO and CaS-25% MgO, CaS-15% MgO and CaS-25% MgO), and the differences between the other pairs were statistically significant.
[0098] 2. Effect on mature biofilm: Add 1 ml of bacterial solution (10 5 CFU / ml) to a 2 ml centrifuge tube and incubate for 3 d to form a mature biofilm. Pour out the bacterial solution, gently rinse the centrifuge tube with PBS, then add 1.5 ml of fresh LB broth, tie the sample to a string and suspend it in the broth (avoid mechanical damage to the pre-formed biofilm). After co-culturing for 3 d, discard the broth and the sample, and gently rinse the centrifuge tube with PBS; add 1 ml of methanol to fix for 15 min, discard the methanol, and air-dry the centrifuge tube; add 1 ml of 1% (w / v) crystal violet solution to stain for 15 min, and repeatedly rinse with PBS until the rinse solution is colorless. Add 1 ml of the above glacial acetic acid to release crystal violet, and measure the absorbance of the solution (590 nm). The results showed that after crystal violet staining, the color of the centrifuge tube wall became shallower in turn with the increase of the MgO ratio in the immersed samples. After eluting crystal violet with glacial acetic acid, the absorbance of the eluate also decreased in turn with the increase of the MgO ratio ( Figure 12)。Compared with the blank control group (without samples), in the antibacterial test of Escherichia coli, the absorbance of each group decreased by 35.9% (CaS), 62.3% (CaS-2.5% MgO), 70.4% (CaS-7.5% MgO), 80.4% (CaS-15% MgO), and 86.5% (CaS-25% MgO), respectively; in the antibacterial test of Staphylococcus aureus, the decreases were 31.7%, 38.9%, 45.0%, 47.1%, and 65.7%, respectively. For Escherichia coli, there were statistically significant differences between the blank control and the four MgO-containing groups, and there was a statistically significant difference between CaS and the two groups with the highest MgO content (CaS-15% MgO, CaS-25% MgO). There were no statistically significant differences among the remaining groups. For Staphylococcus aureus, there were statistically significant differences between the blank control group and the three groups with the highest MgO content (CaS-7.5% MgO, CaS-15% MgO, CaS-25% MgO), and between CaS and CaS-25% MgO; there were no statistically significant differences among the remaining groups.
[0099] V. Biocompatibility evaluation
[0100] 1. Preparation of extraction solution: The samples were immersed in α-MEM medium (Gibco, USA) at a solid-liquid ratio of 0.2 g:1 ml and left standing in a cell culture incubator for 72 h, and then filtered through a 0.2-μm microporous membrane (Millipore, USA) to prepare the extraction solution.
[0101] 2. Cell proliferation assay: 10% (v / v) fetal bovine serum (Gibco, USA) and 1% (v / v) penicillin-streptomycin solution (Beyotime Biotechnology, Shanghai) were added to the above extraction solution. MC3T3 cells were resuspended in this solution or complete medium (negative control) and adjusted to 10 4 cells / ml. 200 μl of the cell suspension was added to a 96-well plate, and after incubation for 24, 48, and 72 h, 20 μl of CCK-8 reagent (Baoguang Biology, Chongqing) was added to each well, and the absorbance at 450 nm was measured after incubation at 37 °C for 1.5 h.
[0102] Results: Figure 13The results showed that at all time points, the cell viability decreased successively with the increase in the proportion of MgO. Compared with the negative control, the cell viabilities of CaS, CaS-2.5% Mg, and CaS-7.5% MgO were all > 76%; according to ISO10993-5, these three groups had no cytotoxicity within 3 days. The cell viability of the CaS-15% MgO group was > 0.73 on the 1st and 2nd days, and decreased to 0.69 on the 3rd day, indicating that this sample had slight cytotoxicity on the 3rd day. The viability of CaS-25% MgO remained at 0.65 - 0.68, indicating that this group had mild cytotoxicity. Except for the difference between one pair of groups (CaS-15% MgO and CaS-25% MgO) at the 3rd day, the differences between all other pairs at any time point were statistically significant.
[0103] 3. Live and dead cell staining experiment: Add 1 ml of cell suspension to a 12-well plate. After incubating for 24 h to allow the cells to adhere, replace the culture medium with the above-mentioned culture solution (2.6.2) or complete culture medium (negative control), and incubate for 24 h and 72 h respectively. Aspirate the culture medium, rinse each well with PBS, and then add 100 μl of cell live and dead staining solution (Wuhan Sevier Biotechnology). Incubate in the dark for 20 min, aspirate the staining solution, and then rinse with PBS. Take pictures under a fluorescence microscope and count (ImageJ 1.54b) the live (green) and dead cells (red), and calculate the proportion of live cells.
[0104] The results showed that after co-culturing with the sample extract for 3 days, the proportion of dead cells (red fluorescence) increased with the increase in the proportion of MgO ( Figure 14 ). The proportions of dead cells in each group were 2.3 ± 0.5% (negative control group), 4.0 ± 0.8% (CaS), 5.7 ± 0.2% (CaS-2.5% MgO), 7.5 ± 0.9% (CaS-7.5% MgO), 8.7 ± 0.4% (CaS-15% MgO), and 14.8 ± 6.1% (CaS-25% MgO). The differences between three pairs of experimental groups were statistically significant (blank control and CaS-25% MgO, CaS and CaS-25% MgO, CaS-2.5% MgO and CaS-25% MgO), and the differences between the remaining groups were not statistically significant.
[0105] VI. Evaluation of alkaline phosphatase (ALP) expression
[0106] Dexamethasone (Shanghai Sangon Biotech Co., Ltd.) was added to the extraction solution to a concentration of 15 μg / ml, β-glycerophosphate disodium (Shanghai Sangon Biotech Co., Ltd.) to 2.2 mg / ml, and ascorbic acid (Sigma, USA) to 10 μg / ml to form an osteogenic induction medium. MC3T3 cells were seeded in 24-well plates and incubated until the confluence reached ~90%. Then the medium was replaced with the osteogenic induction medium. After culturing for 7 days, the medium was aspirated, the wells were rinsed with PBS, and the cells were fixed with paraformaldehyde (Shanghai Macklin Biochemical Co., Ltd.) for 15 min. After aspirating the paraformaldehyde, the wells were rinsed again with PBS, and 100 μl of ALP staining reagent (Shanghai Beyotime Biotechnology Co., Ltd.) was added. After incubating in the dark for 6 h, the ALP staining of the cells was observed under a microscope.
[0107] As Figure 15 shown, after ALP staining, the bottoms of all wells were stained blue. The group with the darkest staining was the CaS-2.5% MgO group, followed by the CaS-7.5% MgO group and the CaS group. Measuring the gray values of the photos showed that compared with the blank control group, the other groups increased by 23.2% (CaS), 45.3% (CaS-2.5% MgO), 37.7% (CaS-7.5% MgO), 12.4% (CaS-15% MgO), and 5.7% (CaS-25% MgO), respectively. There was no significant difference in 6 pairs of groups [blank control and the two groups with the highest MgO content, CaS and CaS-7.5% MgO, CaS and CaS-15% MgO, CaS-2.5% MgO and CaS-7.5% MgO, CaS-15% MgO and CaS-25% MgO], while the differences between the remaining groups were statistically significant.
[0108] VII. Evaluation of angiogenic ability
[0109] Each group of samples was soaked (0.2 g: 1 ml, 37 °C) in endothelial cell medium for 72 h to prepare an extraction solution. After filtration, 1% (v / v) endothelial cell growth factor, 1% (v / v) penicillin-streptomycin, and 10% (v / v) fetal bovine serum (all from Sciencell, USA) were added. Human umbilical vein endothelial cells (HUVECs, Zhejiang Meisen Cell Technology Co., Ltd.) were cultured in 6-well plates until the confluence reached ~90%, and then the medium was replaced with the above extraction solution and cultured for another 3 days. After digestion, the cells in each group were resuspended with the medium and adjusted to 5×10 4cells / ml. Matrigel (Xiamen Jimo Biotechnology) was thawed overnight in a 4°C refrigerator and mixed with pre-cooled α-MEM medium (α-MEM / Matrigel = 1 / 2, v / v), and added to a 96-well plate (100 μl / well) (operation on ice). The plate was placed in a 37°C incubator. After the liquid in the wells solidified, 150 μl of HUVEC cell suspension was added. After incubation for 4 h, the tube formation and branching of the cells were observed under a microscope. After washing the plate with PBS, calcein staining reagent (20 μl / well, Wuhan Sevier Biotechnology) was added, and after incubating in the dark for 20 min, the surface of the Matrigel was washed with PBS, and the tube formation and branching were observed under a fluorescence microscope.
[0110] After staining the HUVECs on the Matrigel, the cells were green under a fluorescence microscope, and the cells intertwined to form a network ( Figure 16 ). The formed branches were counted to quantitatively evaluate the angiogenesis ability of each group. It was found that the number of branches in each group first increased and then decreased with the increase of the MgO ratio, and reached the highest value at 7.5% MgO. Compared with the control group, the other groups increased by 84%, 119%, 170%, 78% and 19% in turn. There were statistically significant differences among 3 pairs of experimental groups [blank control and the 2 groups with the lowest MgO content, CaS-7.5% MgO and CaS-25% MgO], and there were no statistically significant differences among the remaining groups.
[0111] VIII. Antibacterial Activity Test in Vivo
[0112] Thirty male SD rats (∼220 g) (source: Experimental Animal Center of Southwest Medical University) were randomly divided into 5 groups (n = 6 / group). After anesthesia, they were placed in the prone position, the hair on the left hip was shaved, disinfected, and a skin incision of ∼1.5 cm was made and deepened into the muscle. The sample (Φ5 × 5 mm) was immersed in a Staphylococcus aureus solution with a concentration of 10 5 CFU / ml for 1 min, taken out and implanted into the muscle incision, and the wound was sutured layer by layer. After 1 and 3 days, the animals were euthanized and sampled. The samples and adjacent muscle tissues were washed with 300 μl of PBS, the washing solution was spread on an agar plate, incubated for 24 h, and the formed colonies were counted. In addition, the wounds of the animals sacrificed on the 3rd day were observed for redness, swelling and pus; the muscle tissues around the samples were excised, sections were made, stained with hematoxylin-eosin (HE), and histological examination was performed.
[0113] Compared with the CaS group, less colonies were formed in the irrigation fluid of other groups, and it decreased with the increase of MgO dosage. Compared with the CaS group, the antibacterial rates on the 1st day were 80.3±8.6%, 82.8±6.8%, 88.8±6.2% and 97.2±2.5% successively from the CaS-2.5% MgO group to the CaS-25% MgO group. The antibacterial rates on the 3rd day were 84.1±1.6%, 85.6±0.2%, 98.2±1.1% and 98.9±0.6% successively. At the two time points, the differences between the CaS group and any MgO-containing group were statistically significant, while there were no statistically significant differences among the other groups.
[0114] On the 3rd day after implantation, all skin incisions were partially healed and there was no purulent exudation. After the skin was incised, abscesses appeared in the muscles of 2 rats implanted with CaS, while the other animals showed normal conditions. HE staining showed that there was no necrosis or disintegration of muscle cells near all samples; however, compared with other groups, there was more severe inflammatory cell aggregation and inflammatory exudation in the muscle tissue of the CaS group. In addition, the white blood cell counts in the muscle sections around the samples of each group were 22.6% lower than that of the CaS group (CaS-2.5% MgO), 31% (CaS-7.5% MgO), 39% (CaS-15% MgO), 46.1% (CaS-25% MgO)( Figure 17 ). The differences between the CaS group and the three groups with the highest MgO content were statistically significant, while there were no statistically significant differences among the other groups.
[0115] In summary, the α-calcium sulfate hemihydrate composite material of the present invention exhibits beneficial effects such as good antibacterial performance and biocompatibility.
[0116] It should be understood that various forms of the processes shown above can be used, reordering, adding or deleting steps. For example, the steps recorded in the disclosure of the present invention can be executed in parallel, sequentially or in different orders, as long as the desired results of the technical solutions disclosed in the present invention can be achieved, and no limitations are imposed herein.
[0117] The above specific embodiments do not constitute a limitation to the protection scope of the present invention. Those skilled in the art should understand that various modifications, combinations, sub-combinations and substitutions can be made according to design requirements and other factors. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention shall be included within the protection scope of the present invention.
Claims
1. A preparation method of an α-calcium sulfate hemihydrate composite material, characterized in that Specifically, it includes the following steps: S1. Add sodium citrate and calcium sulfate hemihydrate to deionized water, mix evenly, and heat at 120 - 140 °C for 100 - 150 min; S2. Place the mixed solution in step S1 in water not lower than 95 °C for repeated washing and precipitation, then dry and crush the precipitate to obtain α-calcium sulfate hemihydrate powder; S3. Mix MgO with α-calcium sulfate hemihydrate powder to obtain an α-calcium sulfate hemihydrate composite, where the mass fraction of MgO is 2.5 - 25%; S4. Mix the two according to the ratio of the α-calcium sulfate hemihydrate composite to distilled water to make a slurry, pour it into a mold, and form a columnar sample through curing, which is the α-calcium sulfate hemihydrate composite material.
2. The preparation method of an α-calcium sulfate hemihydrate composite material according to claim 1, characterized in that, The mass ratio of sodium citrate to calcium sulfate hemihydrate is 1:250 - 300.
3. The preparation method of an α-calcium sulfate hemihydrate composite material according to claim 1, characterized in that, The mass ratio of sodium citrate to calcium sulfate hemihydrate is 1.5:
400.
4. The preparation method of an α-calcium sulfate hemihydrate composite material according to any one of claims 1 to 3, characterized in that, In step S1, the heating temperature is 134 °C and the heating time is 120 min.
5. The preparation method of an α-calcium sulfate hemihydrate composite material according to claim 4, characterized in that, In step S1, the drying method is drying in an oven, the drying temperature is 100 °C, and the time is 24 h; the crushing is carried out by high-speed crushing with a wall breaker.
6. The preparation method of an α-calcium sulfate hemihydrate composite material according to claim 1, characterized in that, In step S3, the mass fraction of MgO is 15 - 25%; the particle size of MgO is 50 nm.
7. The preparation method of an α-calcium sulfate hemihydrate composite material according to claim 1, characterized in that, In step S4, the ratio of the α-calcium sulfate hemihydrate composite to distilled water is 2 - 3 g:1 mL.
8. The preparation method of an α-calcium sulfate hemihydrate composite material according to claim 1, characterized in that, The curing in step S4 is high-temperature curing, the curing temperature is 90 - 100 °C, and the curing time is 4 - 8 hours.
9. The preparation method of an α-calcium sulfate hemihydrate composite material according to claim 1, wherein, The α-calcium sulfate hemihydrate powder is a short rod-shaped crystal, with a length of 50 - 80 μm and a diameter of 20 - 40 μm; the mold specifications are Φ5×5 mm, Φ5×10 mm or Φ10×10 mm.
10. An α-calcium sulfate hemihydrate composite material, characterized in that, Prepared by using the preparation method of an α-calcium sulfate hemihydrate composite material described in any one of claims 1 - 9.